BIM and integrated design strategies for architectural practice - Deutsch, Randy (Wiley, 2011)
"Building Information Modeling (BIM) software combines 3-D elements and information in all aspects of the design of a building.While many books are published on BIM related to technology and computer programs, this one focuses on the practice-related information needs of architects, showing them how BIM and integrated practice can transform their practices. It features: Methods for addressing the obstacles and challenges to implementing BIM How to implement it in an efficient and effective manner How to use BIM as a tool to transform the role of architects "--